Current Challenges for Home Loans in India - Maheshwari, Neeta; Biyani, Rajeev (Indian Journal of Finance, 2011)
The major objective of this paper is to provide crucial information for getting home loans for housing in our country and improve the living standard of communities. This task is very important in several aspects, for example, it sheds light on the issue of affordability of a house as a major aspect of the overall poverty problem and ways to combat it; and, it enables us to stress on the importance of the need for more flexible lending practices among banks. The work presented here highlights and analyzes the challenges and problems faced by borrowers. Influence of inflation on interest rate of housing loan is discussed. Also, best available options for borrowers (such as EMI, prepayment) as per their financial capacity are discussed. This is based on the current market scenario, past trends and rules&regulations laid by RBI. Also, various options for lenders are discussed. In general, as inflation increases, home loan interest rate increases. Home loan interest rates also influence the terms of loans. Fixed interest rates are higher than the floating interest rates. Interest rate increases with the increase in tenure of the loan. Rate is higher for higher amount of loan. Decline in interest rates stimulates both the demand and supply of mortgage loans. Advances in information technology with financial innovations have created higher efficiency.